Pengembangan Big Book Berbasis Value Clarification Technique (VCT) dalam Meningkatkan Bernalar Kritis Siswa Kelas IV di MI Al-Kautsar Joho Kabupaten Madiun - Mulyoto, Galih Puji; Muhammad Nur Kholilul , Firdaus; Damayanti, Setia; Ayu Puspitasari, Debi (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to create and develop VCT-based big book learning media to improve critical reasoning of students in Class IV of MI Al Kautsar Joho, Madiun Regency. This study was conducted in Class IV of MI Al Kautsar Joho, Madiun Regency. This study uses development (Research and Development). The results of this study are Bigbook Learning Media using the VCT model with a percentage increase in learning outcomes and students' critical reasoning abilities (1) in the pretest, the average student learning outcomes obtained a score of 59.7. While the posttest results showed that all students got scores above the KKM (KKM = 75) with an average class score of 80.8. This shows a success in learning in terms of cognitive aspects with an average increase in learning outcomes of 26%, (2) The results shown by the pretest results of 27 class IV students showed an average of 449 out of 540. This shows a success in learning in terms of cognitive aspects with an average increase in learning outcomes of 83% or in the good category. Conclusion: Big Book Learning Media using the Value Clarification Technique (VCT) model is very suitable for use in the learning process and is able to improve students' critical reasoning patterns in the diversity material of Class IV MI Al Kautsar Joho, Madiun Regency.